Screening of Geomechanical Risks for Malaysian Development Field - Syed Najmuddin, S.M.S. (EDP Sciences, 2016)
Deeper drilling and exploitation of difficult reservoir is the new trend in oil and gas industry. Geomechanics study has, therefore, become a new requirement particularly for oil and gas field development. However, a complete geomechanics study is limited with the number of experts, time consuming and not a straightforward task. Therefore, there is an urgent need of a quick geomechanics screening criterion to be used as a standard guideline to evaluate the high level geomechanical risks and suitable analysis can be recommended for the identified development fields. The aim of this paper is to propose a screening criterion for geomechanical risks study based on four key parameters, drilling, depletion, injection and storage and sand production. The screening approach is designed based on Risk Assessment Matrix (RAM) risk screening where the likelihood is based on a set of scores developed to specific questions. The consequence for each failure scenarios is assessed based on educated estimation of the impact towards people, asset, environment and reputation. Recommendations for geomechanical study are made based on the severity of each failure category on the RAM risk matrix. Fourteen development fields in offshore Peninsular Malaysia, offshore Sarawak and offshore Sabah are selected for the assessment. Based on results, fields in offshore Sarawak and Sabah have higher potential for geomechacnical issues mainly because of their geological settings and formation characteristics. A set of geomechanical study is proposed for each individual field for prudent management of potential geomechanics risk associated with the depletion and EOR injection scheme planned for the fields. Â© The Authors, published by EDP Sciences, 2017.